Exocytosis of gold nanoparticle and photosensitizer from cancer cells and their effects on photodynamic and photothermal processes. (12th April 2018) - He, Yulu; Hua, Wei-Hsiang; Low, Meng-Chun; Tsai, Yu-Hsuan; Cai, Cheng-Jin; Chiang, Hsin-Chun; Yu, Jian-He; Hsiao, Jen-Hung; Tseng, Po-Hao; Kiang, Yean-Woei; Yang, C C; Zhang, Zhenxi
Abstract: We first illustrate the faster decrease of the photothermal (PT) effect with the delay time of laser treatment, in which the illumination of a 1064 nm laser effectively excites the localized surface plasmon (LSP) resonance of cell-up-taken gold nanoring (NRI) linked with a photosensitizer (PS), when compared with the photodynamic (PD) effect produced by the illumination of a 660 nm laser for effective PS excitation. The measurement results of the metal contents of Au NRI and PS based on inductively coupled plasma mass spectroscopy and the PS fluorescence intensity based on flow cytometry show that the linkage of NRI and PS is rapidly broken for releasing PS through the effect of glutathione in lysosome after cell uptake. Meanwhile, NRI escapes from a cell with a high rate such that the PT effect decays fast while the released PS can stay inside a cell longer for producing a prolonged PD effect. The effective delivery of PS through the linkage with Au NRI for cell uptake and the advantageous effect of LSP resonance at a PS absorption wavelength on the PD process are also demonstrated.